The Dialectics of Islam and Custom in the Kenduri La’ōt Tradition of the Coastal Muslim Community of East Aceh - Zubir, Zubir; Bustamam Ahmad, Kamaruzzaman (Jurnal Ilmiah Peuradeun, 2022)
Religion is a sensitive issue for the Acehnese Muslim community. However, the practice of religion and culture of marine safety for coastal communities, primarily fishers, is significant, although sometimes it cannot be separated from magical things. This paper aimed to describe how the religion and customs of salvation run in harmony among the people of East Aceh are solid with the tradition of Islamic law. This research results from an empirical study with a phenomenological approach that seeks to see people’s behavior in celebrating marine safety. The source of the data was obtained from the coastal communities of East Aceh who were directly involved with the practice of the kenduri laot tradition. Empirical research was conducted on a coastal Muslim community located in the eastern part of Aceh. This paper argued that the phenomenon of maritime security carried out by coastal Muslim communities is a tradition that previous people have practiced. However, the coastal Muslim community of East Aceh is very thick with Islamic teachings. However, the marine safety tradition is important because it contains a philosophical aspect still maintained today. The Islamization of the kenduri la’ōt practice wrapped in Islamic events eliminates the mystical impression. This illustrated that there is a dialectic shift from a naturalistic tradition to a theological tradition; the belief that is built by the community is that there is a compromise between tradition and religion to create harmonious conditions, religion becomes the spirit and supporter in the celebration of marine safety, and this is what makes the practice of kenduri la’ōt (sea safety) survive.